Pharmacological modulation of cell death in organ transplantation. (26th June 2017) - Cippà, Pietro E.; Fehr, Thomas
Summary: New options to pharmacologically modulate fundamental mechanisms of regulated cell death are rapidly evolving and found first clinical applications in cancer therapy. Here, we present an overview on how the recent advances in the understanding of the biology and pharmacology of cell death might influence research and clinical practice in solid organ transplantation. Of particular interest are the novel opportunities related to organ preservation and immunomodulation, which might contribute to promote organ repair and to develop more selective ways to modulate allogeneic immune responses to prevent rejection and induce immunological tolerance.